Gene expression responses to Zika virus infection in peripheral blood mononuclear cells from pregnant and non‐pregnant women. Issue 12 (19th November 2020) - Lim, Shen Jean; Seyfang, Andreas; Dutra, Samia; Kane, Bradley; Groer, Maureen
Abstract: Congenital Zika syndrome is caused by mother‐to‐fetus transmission of the Zika virus (ZIKV). Peripheral blood mononuclear cells (PBMCs) are permissive to ZIKV infection and may carry ZIKV to the placenta. To identify pregnancy‐related differences in PBMC responses against ZIKV infection, we compared gene expression profiles of ZIKV‐infected and non‐infected PBMCs cultured from pregnant and non‐pregnant women. ZIKV‐infected pregnant conditions generally overexpressed M1‐shifted pro‐inflammatory responses and underexpressed M2‐shifted anti‐inflammatory responses. Additionally, transcripts involved in osteoclast differentiation and cardiac myopathies were upregulated following ZIKV infection. Our results suggest potential roles of pregnancy‐induced immune dysregulation in shaping neonatal pathology associated with ZIKV infection. Abstract : To identify pregnancy‐related differences in peripheral blood mononuclear cell responses against Zika virus infection, we compared gene expression profiles of infected and non‐infected cells cultured from pregnant and non‐pregnant women. Infected pregnant conditions generally overexpressed M1‐shifted pro‐inflammatory responses and underexpressed M2‐shifted anti‐inflammatory responses. Additionally, transcripts involved in osteoclast differentiation and cardiac myopathies were upregulated following Zika virus infection. Our results suggest potential roles of pregnancy‐induced immune dysregulation in shaping neonatal pathology associated with Zika virus infection.